Structures of the N‐Terminal Domain of PqsA in Complex with Anthraniloyl‐ and 6‐Fluoroanthraniloyl‐AMP: Substrate Activation in Pseudomonas Quinolone Signal (PQS) Biosynthesis. (18th September 2017) - Witzgall, Florian; Ewert, Wiebke; Blankenfeldt, Wulf
Abstract: Pseudomonas aeruginosa, a prevalent pathogen in nosocomial infections and a major burden in cystic fibrosis, uses three interconnected quorum‐sensing systems to coordinate virulence processes. At variance with other Gram‐negative bacteria, one of these systems relies on 2‐alkyl‐4(1 H )‐quinolones ( Pseudomonas quinolone signal, PQS) and might hence be an attractive target for new anti‐infective agents. Here we report crystal structures of the N‐terminal domain of anthranilate‐CoA ligase PqsA, the first enzyme of PQS biosynthesis, in complex with anthraniloyl‐AMP and with 6‐fluoroanthraniloyl‐AMP (6FABA‐AMP) at 1.4 and 1.7 Å resolution. We find that PqsA belongs to an unrecognized subfamily of anthranilate‐CoA ligases that recognize the amino group of anthranilate through a water‐mediated hydrogen bond. The complex with 6FABA‐AMP explains why 6FABA, an inhibitor of PQS biosynthesis, is a good substrate of PqsA. Together, our data might pave a way to new pathoblockers in P. aeruginosa infections. Abstract : Gatekeeper of PQS biosynthesis unmasked : We determined the crystal structure of the N‐terminal domain of PqsA, a member of the ANL superfamily that channels anthranilate into the biosynthetic pathway of the quorum‐sensing (QS) molecule Pseudomonas quinolone signal (PQS). The structure might help in the development of specific QS inhibitors for therapeutic treatment.